Coupling of anticipation and breathing in expert flute performance: the influence of musical structure and practice - Cara, Michel A.; Mitrovic, Divna (Frontiers in Cognition, 2024)
In this study, we examined the cognitive processes and physiological responses involved in learning a flute piece by the composer Charles Koechlin among musicians of different expertise levels. Participants performed the piece four times consecutively, with a two-minute practice interval between the first and the second trial. Using data obtained from an eye tracker, respiratory sensors, and an audio recorder we assessed short-term improvement and the effect of musical structure and practice on key variables identified through a multivariate approach: eye-hand span (EHS), time index of EHS, thoracic and abdominal amplitude (breathing patterns) and pupil dilation. The analysis revealed two main dimensions: one associated with EHS; and the other with embodied responses to music, closely linked to breathing patterns and pupil dilation. These insights support the hypothesis of a coupling between anticipation and breathing, emphasizing the role of perceptual and embodied components in music reading and learning. We found an effect of musical structure on all the variables studied, while the EHS improved with practice. Expert musicians demonstrated enhanced EHS, allowing them to adapt their breathing patterns more effectively to the music's structure.